2008
DOI: 10.1124/jpet.107.135764
|View full text |Cite
|
Sign up to set email alerts
|

Vascular KCNQ Potassium Channels as Novel Targets for the Control of Mesenteric Artery Constriction by Vasopressin, Based on Studies in Single Cells, Pressurized Arteries, and in Vivo Measurements of Mesenteric Vascular Resistance

Abstract: Pressor effects of the vasoconstrictor hormone arginine vasopressin (AVP), observed when systemic AVP concentrations are less than 100 pM, are important for the physiological maintenance of blood pressure, and they are also the basis for therapeutic use of vasopressin to restore blood pressure in hypotensive patients. However, the mechanisms by which circulating AVP induces arterial constriction are unclear. We examined the novel hypothesis that KCNQ potassium channels mediate the physiological vasoconstrictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
209
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(228 citation statements)
references
References 45 publications
17
209
2
Order By: Relevance
“…In support of our hypothesis, celecoxib induced concentration-dependent, endothelium-independent dilation of pre-constricted mesenteric arteries. Similar effects were obtained using known L-type Ca 2+ channel blockers or activators of Kv7 channels (not shown, but see (Henderson & Byron, 2007;Mackie et al, 2008)). The maximum dilatory effect of celecoxib was achieved at a concentration of 20 µM; neither rofecoxib nor diclofenac induced significant artery dilation at the same concentration ( Figure 2B).…”
Section: Molecular Biological Approaches To Evaluate Kv75 As a Targesupporting
confidence: 53%
“…In support of our hypothesis, celecoxib induced concentration-dependent, endothelium-independent dilation of pre-constricted mesenteric arteries. Similar effects were obtained using known L-type Ca 2+ channel blockers or activators of Kv7 channels (not shown, but see (Henderson & Byron, 2007;Mackie et al, 2008)). The maximum dilatory effect of celecoxib was achieved at a concentration of 20 µM; neither rofecoxib nor diclofenac induced significant artery dilation at the same concentration ( Figure 2B).…”
Section: Molecular Biological Approaches To Evaluate Kv75 As a Targesupporting
confidence: 53%
“…HeLa cells were as described (70). Rat aortic and mesenteric artery VSMC were isolated from male Lewis and Sprague-Dawley rats as described elsewhere (71)(72)(73). All procedures involving rats were in accordance with the Guide for the Care and Use of Laboratory Animals and approved by the Institutional Animal Care and Use Committee of Loyola University Chicago.…”
Section: Methodsmentioning
confidence: 99%
“…In vascular smooth muscle cells, KCNQ1, KCNQ4 and KCNQ5 are predominantly expressed with a minimal contribution of KCNQ2 and KCNQ3. [46][47][48] In addition, Jepps et al 49 recently demonstrated that KCNQ channel activators induce arterial relaxation, and the expression of KCNQ4 is decreased in the vascular smooth muscle cells of hypertensive rodent models. The present study also suggested that perivascular sympathetic neurotransmission might also be influenced by KCNQ channels in rat mesenteric arteries.…”
Section: Kcnq Channels In Perivascular Sympathetic Nerves Y Kansui Et Almentioning
confidence: 99%